The use of a biologic topical haemostatic agent (TachoSil®) for the prevention of postoperative bleeding in patients on antithrombotic therapy undergoing thyroid surgery: A randomised controlled pilot trial. (August 2015) - Erdas, Enrico; Medas, Fabio; Podda, Francesco; Furcas, Silvia; Pisano, Giuseppe; Nicolosi, Angelo; Calò, Pietro Giorgio
Abstract: Introduction: Anticoagulants and antiplatelet agents are well-known risk factors for post-operative bleeding. The aim of this prospective, randomized pilot study was to evaluate the effectiveness of a topical haemostatic agent, namely TachoSil, for the prevention of postoperative bleeding in patients on antithrombotic therapy undergoing thyroidectomy. Perioperative management and some distinctive aspects of cervical haematomas were also discussed. Methods: Between January 2012 and May 2014, all patients taking vitamin K antagonists (VKAs) or acetyl salicylic acid (ASA) scheduled for total thyroidectomy were enrolled and randomly allocated to group 1 (standard haemostasis) and group 2 (standard haemostasis + TachoSil). Antithrombotic drugs were always suspended prior to surgery and, when indicated, replaced by bridging anticoagulation with low-molecular-weight heparin. The primary endpoint was the incidence of postoperative cervical haematomas. Results: A total of 70 patients were included in the study, representing 8.5% (70/820) of all patients who underwent thyroidectomies in the same period. The overall rate of post-operative cervical haematoma was 7.1% (5/70) and reached 14.8% (4/27) in patients on VKA therapy. All but one occurred more than 24 h after surgery (32nd hour, 8th, 10th, and 13th days). Group 1 (37 patients) and group 2 (33 patients) were well-matched according to clinical and demographic features. Postoperative haematoma was observed in 2/37 patients (5.4%) recruited in the Group 1 and 3/33 patients (9.1%) recruited in the Group 2 ( P = 0 . 661 ). Conclusions: Patients taking antithrombotic drugs represent a major problem in thyroid surgery. The incidence of bleeding after thyroidectomy is significantly high and the use of TachoSil do not seem effective in preventing its occurrence. However, larger multicenter study is needed to confirm these results. Highlights: Patients on antithrombotic therapy are at high risk of post-operative bleeding. The role of TachoSil in preventing bleeding after thyroidectomy was evaluate in such patients. The overall rate of post-operative cervical haematoma was 7.1% (5/70 patients). In 3 out 5 cases bleeding occur several days after surgery (8th, 10th and 13th post-operative day). TachoSil has not proven to be more effective then standard haemostasis.